Lived experiences and drivers of induced abortion among women in central Uganda. - Simon Peter Sebina Kibira; Melissa Stillman; Fredrick E Makumbi; Margaret Giorgio; Sarah Nabukeera; Grace Kigozi Nalwoga; Elizabeth A Sully (PLOS Global Public Health, 2023)
Although unsafe abortions are preventable, they are one of the leading causes of maternal mortality and morbidity. Despite the serious potential health consequences, there is limited published information about drivers and challenges of obtaining abortions in restrictive settings such as Uganda. This limits efforts to improve programing for preventing unsafe abortion and providing comprehensive post abortion care. This study sought to understand the drivers and explain the lived abortion experiences among women from central Uganda, in an effort to promote greater access to safe reproductive healthcare services, and reduce unsafe abortions. This qualitative study included 40 purposely selected women who self-reported an abortion, living in Kampala and greater Rakai district, Uganda. They were part of a larger survey using respondent driven sampling, where seed participants were recruited from selected facilities offering post-abortion care, or through social referrals. Data were collected from May to September 2021 through in-depth interviews. Audio data were transcribed, managed using Atlas.ti 9, and analyzed thematically. The findings show that the underlying drivers stemmed from partners who were unsupportive, denied responsibility, or had raped/defiled women. Career and education decisions, stigma and fear to disappoint family also contributed. Women had feelings of confusion, neglect, betrayal, or shame after conception. Abortion and post-abortion experiences were mixed with physical and emotional pain including stigma, even when the conditions for safe abortion in the guidelines were satisfied. Although most women sought care from health facilities judged to provide safe and quality care, there was barely any counselling in these venues. Confidantes and health providers informed the choice of abortion methods, although the cost ultimately mattered most. The mental health of women whose partners are unsupportive or who conceive unintendedly need consideration. Abortion provided psychological relief from more complicated consequences of having an unplanned birth for women.